2018
DOI: 10.21009/jrmsi.009.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Motivasi Kerja Dan Kompensasi Terhadap Kepuasan Kerja Pada Karyawan Pt Tridaya Eramina Bahari

Abstract: Tujuan penelitian ini adalah: 1) Untuk mengetahui deskripsi motivasi kerja, kompensasi dan kepuasan kerja pada karyawan PT Tridaya Eramina Bahari, 2) Untuk mengetahui apakah terdapat pengaruh antara motivasi kerja terhadap kepuasan kerja pada karyawan pada PT Tridaya Eramina Bahari, 3) Untuk mengetahui apakah terdapat pengaruh antara kompensasi terhadap kepuasan kerja pada karyawan PT Tridaya Eramina Bahari, 4) Untuk mengetahui motivasi kerja dan kompensasi dapat memprediksi kepuasan kerja pada karyawan pada P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
28

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 0 publications
3
7
0
28
Order By: Relevance
“…This hypothesis is accepted because the t-statistics value of 4.629 is greater than 1.96 and the P value of 0.000 is smaller than 0.05. This is supported by previous research conducted by Parimita et al (2018) and also Akmal and Tamini (2015) which states that there is a positive influence between compensation and job satisfaction.  Hypothesis 2: Supervisor support has an effect to job satisfaction.…”
Section: Q-square Testsupporting
confidence: 85%
“…This hypothesis is accepted because the t-statistics value of 4.629 is greater than 1.96 and the P value of 0.000 is smaller than 0.05. This is supported by previous research conducted by Parimita et al (2018) and also Akmal and Tamini (2015) which states that there is a positive influence between compensation and job satisfaction.  Hypothesis 2: Supervisor support has an effect to job satisfaction.…”
Section: Q-square Testsupporting
confidence: 85%
“…Sedangkan menurut (Marta & Budi, 2019), lingkungan sekitar karyawan bekerja yang berupa fisik tidak berpengaruh secara signifikan terhadap kepuasan kerja karyawan. Afandi (2016: 12) (Diyanti et al, 2015), Parimita et al, (2018)…”
Section: Pendahuluanunclassified
“…A positive attitude can make motivation levels higher and trigger job satisfaction. The results show that work motivation has a positive relationship and significant effect on job satisfaction (Rozzaid et al, 2015;Maurya & Agarwal, 2018;Parimita et al, 2018). However, research done long before the pandemic and during the pandemic found exciting findings when employees are accustom to the new environment, such as work from home.…”
Section: Introductionmentioning
confidence: 99%